IMPLEMENTASI SAK-ETAP PADA LAPORAN KEUANGAN USAHA KECIL DAN MENENGAH (UKM) TOKO BINGKE KHATULISTIWA - B51112034, Wahyu Ananto Anugrah (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Financial report serves as a tool to analyze financial performance that can provide information about the financial position, performance and cash flows, so it can be used as a basis for making economic decisions. Research aimed at UKM Bingke Khatulistiwa shop that do not have the financial statements. The purpose of this study was to determine how the application of Financial Accounting Standards Entities Without Public Accountability (SAK ETAP) in the preparation of financial statements in UKM Bingke Khatulistiwa shop and any constraints faced by UKM in preparing financial statements based SAK ETAP. This study used a qualitative descriptive method of data collection techniques are interviews, documentary studies, and research literature. It can be concluded that UKM Bingke Khatulistiwa shop is not yet fully comply with and not in accordance with Financial Accounting Standards Entities Without Public Accountability (SAK ETAP). Constraints faced by UKM in the implementation of the financial statements is due to the lack of technical knowledge in preparing the financial statements, lack of education about how the implementation of ETAP SAK on UKM and the lack of oversight of the parties interested in the financial statements of UKM. Keywords : Financial Statements, SAK ETAP, UKM